Identifikasi Kemampuan Multipel Representasi Mahasiswa Calon Guru Fisika - Marpaung, Nurliana; Liliasari, Liliasari; Setiawan, Agus (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2016)
The purpose of this study is to identify the profile of multiple representations ability of  prospective physics teachers in solving physics problems. Study subjects were 35 undergraduate students who have followed the general physics course.  The study was conducted at an LPTK in North Sumatra. The research method is descriptive method. The ability of MR profile  prospective teacher includes the format: 1) verbal representation; 2) mathematical representation; 3) representation of  graph, and 4) a pictorial representation (drawing/ diagram). The research instrument consists of 16 item multiple choice questions with 5 options (are four items for each representation format). The quality of student representation capability based on the accumulated answer to each student representation format qualitatively made in four categories, namely: 1) excellent with a score of 4; 2) good category with a score of 3; 3) poor category with a score of 2; and 4) the category of very poor with score of £ 1. The study results indicate that the ability of the highest student representation is the ability of the mathematical representation (80.0% in a good and excellent categories). The next representation ability is verbal representation (71,40% in the good and excellent category). While the pictorial representation of only 34.4% which is in the good and excellent category and 65.6% is still in the poor and very poor category. The lowest representation ability is the graphical representation format (only 22.9% in good, while 77.1% are in poor and very poor category. The average scores from the highest to the lowest are: mathematical representation,  2.91; verbal representation, = 2.74; pictorial representation, = 2.26, and the graphical representation of = 1.89..Keywords:      multipel representasi, representasi verbal, representasi matematis, representasi grafik, representasi piktorial